ASEAN FTA: Bane or Boon to Cambodia’s Exports - Him Sophal (Graduate School of International Studies Ajou University, 2014)
Association of South East Asian Nations (ASEAN), established in 1967, aims at promoting socio-economic development and preserving regional peace. ASEAN accumulates the aggregate GDPs as the world’s 7th largest economy. Later, ASEAN Free Trade Agreement (ASEAN FTA or AFTA) was singed on January 28th, 1992 in Singapore. AFTA created a trade bloc among 10 member states of ASEAN. The purpose was to eliminate both trade and non-trade barriers within ASEAN. There are two stages of tariff concession within ASEAN region: 0-5% by 2010 and 0% by 2015. AFTA is believed to be stepping stones toward the other site of economic development, yet Cambodia has been perceived as a poor and less-competitive member. Cambodian growth has been driven by export-led economy, so the analysis of impact of AFTA upon the country’s exports play a major role to indicate if Cambodia could reap the benefit of AFTA. For this purpose, the study applies Different-in-different model (D-I-D) with 30 major export products from 5 ASEAN partners. The empirical findings indicate significant relations between AFTA and Cambodia’s exports to Thailand and the Philippines, while the major ASEAN partners namely Malaysia, Singapore, and Vietnam are revealed with insignificant results. Key words: ASEAN FTA; Exports; Cambodia; D-I-D model
학위논문(석사)--아주대학교 국제대학원 :국제통상학과,2014. 8
Keywords: International Trade